USAHA PENINGKATKAN DAYA BELI KONSUMEN DAN MEMPERKECIL BIAYA PRODUKSI KELOMPOK PENJUAL KUE KELEPON DI DESA PANDEREJO, GEMPOL, KABUPATEN PASURUAN - Suprayitno, Eko Agus; Anshory, Izza (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2016)
Panderejo hamlet located in the village Legok, District Gempol, Pasuru- an, ± 10 km from the Campus II University of Muhammadiyah Sidoarjo. Access roads Panderejo Hamlet smoothly. Many residents in this village who worked as Sales Cakes Kelepon and has done since 10 years ago. This is consistent with the potential of the hamlet Panderejo strategically located around Toll Jasa Marga which is the exit toll towards Pandaan Surabaya, Malang, Jember, Probolingggo, Banyuwangi and Bali. In this dedication program raised issues 2 Partners, which Partner 1 is the seller Cakes Kelepon and Partner 2 is a supplier of raw materials kelepon. It is known that there are 9 (nine) problems faced Mitra, from 9 problems there are 5 major issues that must be resolved, the following problems and solutions that have been realized in community service: (1) assist partner 1 in view to make it more attractive Store Front attract customers by adding storefront in front of the store; (2) provide wallpaper wall decoration to beautify stores; (3) giving innovation cake flavors kelepon on partner 1, to relieve the boredom of the buyer against the original flavor of cake kelepon; (4) provide coconut shell peeler machine at partner 2 to help ease the process of stripping oil; (5) increase production capacity reduce the cost of materials and production of raw material prices, namely kelepon cake of glutinous rice flour with glutinous rice penyelep machine availability groats become glutinous rice flour; (6) provide training on the partner's financial administration system in order to determine the development of the business as well as facilitate the partner to access bank funds for the development of kelepon pastry enterprises